2015
DOI: 10.1016/j.cell.2015.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hematopoietic Stem Cell Transplantation Efficacy by Mitigating Oxygen Shock

Abstract: Summary Hematopoietic stem cells (HSCs) reside in hypoxic niches within bone marrow and cord blood. Yet, essentially all HSC studies have been performed with cells isolated and processed in non-physiologic ambient air. By collecting and manipulating bone marrow and cord blood in native conditions of hypoxia, we demonstrate that brief exposure to ambient oxygen decreases recovery of long-term repopulating HSCs and increases progenitor cells, a phenomenon we term Extra Physiologic Oxygen Shock/Stress (EPHOSS). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
285
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(300 citation statements)
references
References 79 publications
(94 reference statements)
14
285
0
1
Order By: Relevance
“…16 Takubo et al 4 found a defect in HSC self-renewal upon Hif-1a deletion and suggested that Hif-1a is an important mediator of HSC functions. Here we set out to acutely induce deletion of Hif-1a in the hematopoietic system and determine its short-and long-term impact on HSC maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…16 Takubo et al 4 found a defect in HSC self-renewal upon Hif-1a deletion and suggested that Hif-1a is an important mediator of HSC functions. Here we set out to acutely induce deletion of Hif-1a in the hematopoietic system and determine its short-and long-term impact on HSC maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis inhibition might be feasible at different levels of the signaling cascade: (a) engagement of upstream protective pathways (i.e., cytokines); (b) inhibition of detrimental signals (i.e., ROS inhibition); or (c) modulation of Bcl-2 protein levels. In contrast, apoptosis inhibition on a more downstream level (i.e., caspase activation) might not be sufficient to ensure survival as noncaspasedependent forms of cell death could be engaged upon mitochondrial damage [159,160].…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…A variety of studies have been conducted to investigate the influence of oxygen concentration on the function of HSCs. HSCs are distributed in the bone marrow and umbilical cord blood which possess a hypoxic environment, but the separation and culture of HSCs are usually performed in non-physiological conditions [44,45]. The exposure of bone marrow and umbilical cord blood to normoxia may induce the differentiation of HSC, and reduce the efficiency of HSC expansion, which is also known as extraphysiologic oxygen shock/stress (EPHOSS).…”
Section: Oxygen Concentrationmentioning
confidence: 99%
“…The exposure of bone marrow and umbilical cord blood to normoxia may induce the differentiation of HSC, and reduce the efficiency of HSC expansion, which is also known as extraphysiologic oxygen shock/stress (EPHOSS). In the harvest of HSCs, the addition of cyclosporine A may protect HSCs against EPHOSS, which increases the proliferation capability and transplantation efficiency of HSCs [45].…”
Section: Oxygen Concentrationmentioning
confidence: 99%